The World Economy: Dr. Pangloss vs. Jeremiah - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "The World Economy: Dr. Pangloss vs. Jeremiah," written by Walter B. Wriston for the Institute of Directors on 25 October 1974. The original speech is located in MS134.001.002.00031.